P-539 Effects of gender of chromosomal translocation's carrier on pre-implantation genetic testing for structural rearrangement (PGT-SR) outcomes. (30th June 2022) - Houissa Ediss, H; Reignier, A; Lammers, J; Moradkhani, K; Freour, T; Loubersac, S
Abstract: Study question: Do the outcomes of PGT-SR cycles vary according to the gender of chromosomal translocation's carrier? Summary answer: The rate of balanced embryos was significantly higher when translocation carrier was a male as compared to female, but clinical outcomes were not significantly different. What is known already: It has been well described that chromosomal translocations lead to very high rate of unbalanced embryos, and have a subsequent negative impact on blastulation, implantation, miscarriage and live birth rates.PGT-SR allows selecting balanced embryos and increases the chances of pregnancy, while decreasing the risk of micarriage in couples with chromosomal translocations. However, whether the gender of translocation carrier is associated with significantly different impact on PGT-SR outcomes is not known. Study design, size, duration: This is a monocentric retrospective cross-sectional study conducted in all PGT-SR cycles performed between 2015 and 2020. A total of 603 cycles, carried out in 283 couples, were included in the analysis. Participants/materials, setting, methods: Two groups have been formed according to the gender of translocation carrier, Group 1 for female carriers (107 couples, 229 cycles), and group 2 for male (175 couples, 373 cycles). The rate of balanced embryos, ovarian stimulation parameters, number of oocytes, biopsy rate, clinical pregnancy rate and live birth rate were compared between both groups. Main results and the role of chance: Female age and infertility etiologies were comparable between both groups. Mean total dose of gonadotrophin and peak E2 levels were not significantly different in both groups (2422± 895 units vs 2290 ± 858 respectively, p > 0.05) (2460± 1346 pg/ml vs 2497 ± 1397, p > 0.05). There was no significant difference in the number of oocytes and biopsied embryos rate between Group 1 and Group 2. The rate of balanced embryo after PGT-SR was significantly lower in group 1 (female carriers) than in group 2 (21.1% vs 24.8% respectively, p = 0.036 ). Finally, biochemical pregnancy rate and live birth rate per transfer were not statistically different between both groups (46.2% vs 43.2% and 20.3% vs 18.5% respectively, p > 0.05). Limitations, reasons for caution: The retrospective nature of the study was its main limitation. PGT-A was not used, preventing from concluding on embryo euploidy rate. Wider implications of the findings: Further fundamental studies should be performed to explore the respective mechanisms involved in chromosomal rearrangements according to gender. Our study suggests that a higher number of oocytes could be targeted in female translocation carriers in order to increase the probability of obtaining at least one balanced embryo. Trial registration number: 2